Nature of Genetic Variance and Heterosis in Maize - Ahmed A, Ahmed; Zakariya Badir Fathi (Mesopotamia Journal of Agriculture)
Five inbred lines of maize: ZP-707, ZP-670, ZM 7, ZP and ZM-47W.were used  in a half diallel crosses program, the genotypes (5 inbred lines + 10 hybrids) were planted in the fields of the College of Agriculture and Forestry / university of Mosul in the autumn season 2013 by using randomized complete block design with three replications The characters studied were number of days to silk and tassel flowering ,plant height , height of main ear(cm), number of leaves over the main ear, number of leaves for plant ,leaf area(cm2),ear diameter(cm),ear length (cm), number of rows/ear, number of grain/ear,100-grain weight and plant grain yield (gm). The results showed additive variance  differed from zero to the plant height, the height of the main ear, leaf area(cm), number of grain/ear, 100-grain weight, and plant grain yield (gm). The dominance variance differed from zero for all studied traits. (ZM7 × ZP-707) which gave heterosis (based on deviation of hybrids from mid parents and from best parents) for the character of number of days for tassel flowering, Plant height, number of leaves for plant, leaf area(cm2), number of grain/ear, weight of 100 grains (g) and plant grain yield (gm). The degree of dominance was greater than one for most traits.